3‐D Milk Fouling Modeling of Plate Heat Exchangers with Different Surface Finishes Using Computational Fluid Dynamics Codes. Issue 4 (28th May 2012) - Choi, W.; Jun, S.; Nguyen, L.T.; Rungraeng, N.; Yi, H.; Balasubramanian, S.; Puri, V.M.; Lee, J.
<x xml:space="preserve">Abstract</x> ABSTRACT Milk fouling and self‐cleanability of the heat exchanger surface during the pasteurization process has gained attention from industries as well as academia. In particular, the antifouling mechanism associated with plate corrugation profiles causing the extreme turbulent flow scheme and surface coatings to reduce the surface energy is uncertain. This study was aimed to develop a computational fluid dynamics (CFDs) model in three‐dimensional (3‐D) environment, which could estimate antifouling performances of plate heat exchangers (PHEs) during milk pasteurization process. It was the first attempt to simulate the fouling and temperature distribution patterns on realistic corrugated surfaces of PHE unit with different surface treatments. The conventional stainless steel surface and stainless steel plates coated with Lectrofluor 641 and graded Ni‐P‐polytetrafluoroethylene were compared for their antifouling performances. A transient 3‐D fouling model was developed based on heat and mass transfer equations, and fouling kinetics involving diffusion and protein adhesion mechanisms. Pattern and size of corrugations of actual PHE were measured and subsequently used to build 3‐D solid geometry using AutoCAD (Autodesk, San Rafael, CA). The geometry file was meshed using Gambit software (Fluent Inc., Lebanon, NH) and further transferred to CFD codes. Fouling predictions based on chemical kinetics and the temperature‐dependent parameters accounting for different surface energy values were close to experimental data within a maximum prediction error of 7%. The developed 3‐D fouling model is expected to meet the demand of food industries to correlate the surface energy with the self‐cleanability of food thermal process equipments and seek the theoretical solution. PRACTICAL APPLICATIONS Milk‐fouling phenomena of plate heat exchangers (PHEs) result in an increase of energy consumption, extra maintenance, higher labor costs and a decrease in the productivity. In addition, fouling deposits can cause the growth of unwanted microorganisms on the corrugated surfaces of PHEs. In this study, the transient three‐dimensional computational fluid dynamics model was developed to describe fouling phenomena in consideration of realistic corrugation profiles and estimate the amount of surface fouling based on the hydrodynamic and thermodynamic performances of the PHEs and surface characteristics (conventionally uncoated stainless steel [SS‐316] and stainless steel surfaces with Lectrofluor 641 and graded Ni‐P‐polytetrafluoroethylene).